ANALYSIS ISSUE AND CHALLENGE OF COOPERATIVES DURING PANDEMIC ERA - Helmy Sukiswo; Indrawati Yuhertiana; Dwi Suhartini; Maheran Zakaria (TEMA, 2022)
The whole world is currently still battling the Covid-19 pandemic. The role of the government is very important to make policies in dealing with the Covid-19 pandemic. The study aims to examine articles related to the issues and challenges of cooperatives facing the problems of the Covid-19 pandemic crisis. The study used the literature review method to examine several selected articles related to foreign cooperation research that focused on the performance of cooperatives in dealing with problems that arise during the pandemic. The results of the article review, the research found that there are several problems that exist in Indonesian and Malaysian Cooperatives, and cooperatives have the strength of attachment and partnership of their members to survive during the pandemic crisis. This study has limitations in collecting articles that discuss specifically about cooperatives during the pandemic crisis because there are still few studies that discuss this. Therefore, it is recommended for further researchers to add articles related to the pandemic crisis.